2018
DOI: 10.1186/s12903-018-0495-5
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an oral health intervention program for children with congenital heart defects

Abstract: BackgroundChildren with congenital heart defects (CHD) are reported to have poorer oral health compared with healthy children. The aim of the present study was to evaluate the effectiveness of an intensive oral health care program among children with CHD followed from infancy to the age of 5 years, by comparing their oral health status at 5 years with a control group of children with CHD who had not received the program.MethodsIn this longitudinal study, children in western Norway with a need for lifelong foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 38 publications
(54 reference statements)
3
15
0
2
Order By: Relevance
“…These encouraging results of our and other studies 48,61 provide evidence for the necessity of oral hygiene measurements in this patient group with special focus on gingival health to reduce infectious complications. Undoubtedly, there is a need of specific oral hygiene as an accepted first step in this immunocompromised group with its high infectious risk.…”
Section: Discussionsupporting
confidence: 75%
“…These encouraging results of our and other studies 48,61 provide evidence for the necessity of oral hygiene measurements in this patient group with special focus on gingival health to reduce infectious complications. Undoubtedly, there is a need of specific oral hygiene as an accepted first step in this immunocompromised group with its high infectious risk.…”
Section: Discussionsupporting
confidence: 75%
“…Studies have shown increased poor oral hygiene and caries risk in children with CHD. In addition, the prevalence of caries in children with CHD is significantly higher than in healthy children [ 4 , 5 ]. Sivertsen et al found that this impairment of oral health status has systemic dangerous effects in one third of these children, especially episodes of increased bacteremia [ 3 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The result indicates further need for preventive means among caries active children. The need for preventive means among caries active CHD children is well known (Sivertsen et al 2018 ). There is too little awareness of preventative dental care and its importance among this patient population and their parents (Rai et al 2009 ; Saunders and Roberts 1997 ).…”
Section: Discussionmentioning
confidence: 99%